The acid reflux solution : a cookbook and lifestyle guide for healing heartburn naturally - Rodríguez C., Jorge E. (Ten Speed Press, 2012)
" In this combination cookbook and health guide, Dr. Jorge E. Rodriguez-- who suffers from acid reflux himself-- offers a simple plan for controlling reflux, including 100 delicious and reflux-free recipes that promote better health and weight loss. In fact, Dr. Rodriguez lost 35 pounds while writing (and following) the plan for this book. By busting popular myths and drawing on the latest evidence-based research, The Acid Reflux solution provides real heartburn relief even for longtime sufferers"--